Primary human monocytes are stimulated in a pro-atherosclerotic manner in hyperhomocysteine conditions by attenuated PTEN phosphatase function. (3rd October 2022) - Dorenkamp, M; Semo, D; Miao, L; Koch, S; Reinecke, H; Godfrey, R
Abstract: Purpose: Monocytes are essential for atherosclerosis and hereby crucial for the detrimental consequences of cardiovascular diseases like coronary heart disease. Interestingly, homocysteine (HCY) was identified as an idependent risk factor for atherosclerosis development. However, the specific implication of HCY on monocytes has not yet been clarified and was therefore investigated in the present study. Methods: Primary human monocytes, isolated from peripheral blood through the immuno-magnetic method, were treated with a clinically relevant dose of 400 μM HCY for 24 hours. Monocyte migration was investigated with transwell migration assays. Adhesion to inflamed endothelium (HUVECs) was studied under static and physiological flow conditions. Expression of relevant molecules was quantified with Western Blot, RT-qPCR and FACS. 5-azacytidine (AZA) was used to inhibit DNA methyltransferase 1 (DNMT1) and SF1670 to inhibit PTEN. Results: First, we studied monocyte migration phenotype. Under hyperhomocysteine conditons monocytes revealed elevated chemokinesis and enhance chemotaxis towards MCP-1. In addition, monocytes show a pro-adhesive phenotype under HCY treatment which was indicated by heightened adhesion to inflamed endothelial cells, both in static and physiological flow conditions. These data could be sustained by observation of HCY-induced augmented expression of adhesion molecule CD11a on primary human monocytes. Interestingly, we observed decreased PTEN phosphatase function and activity in HCY-treated monocytes, which was reflected downstream in increased activation of AKT at serine 473. Based on these data, it was also possible to induce the pro-migratory phenotype in monocytes by pharmacological inhibition of PTEN alone. Since HCY can modify the methylation status of PTEN and hereby regulates its expression, we inhibited DNMT1 with AZA which could prevent downregulation of PTEN expression by HCY treatment. In addition, through inhibition of DNMT1 HCY-induced aberrant migration and adhesion was rescued. In line with that, HCY-induced pro-migratory and pro-adhesive phenotype was also rescued by co-treatment with the cofactors (30 μM Vitamin B12 and 3 μM folic acid) responsible for homocysteine to methionine catabolism due to normalized PTEN expression. Conclusions: The present work deciphers a previously unknown mechanism how an increased concentration of HCY induces a pro-atherosclerotic activation of monocytes. Accumulation of HCY leads to a methylation-dependent inactivation of PTEN phosphatase. This subsequently causes increased phosphorylation of AKT at serine 473, which results in an augmented migration behaviour of monocytes. At the same time, we were able to reduce HCY-induced aberrant monocyte activation by inhibiting DNTM1 or by interfering with HCY metabolism by adding vitamin B12 or folic acid. In summary, these findings provide a new approach to reset pro-atherosclerotic monocytes in hyperhomocysteinemic conditions. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): IZKF SEED Project 14/20